Tokopedia and Komunikasi Berasa: The Case of ‘Filosofi Pete’ Campaign - Saroso, Dhea Andita Sari; Paramitha, Ni Ajeng Riandia; Putra, Denny Suwarso; Matahari, Frisky Freny; Fudholi, Ata; Senjatiana, Ferdy; Hadinugroho, Farid (Jobmark: Journal of Branding and Marketing Communication, 2023)
Komunikasi Berasa (experientially-meaningful communication) is communication that synergizes messages and experiences with messages by creating a supportive atmosphere that creates deep meaning and impressions. This article analyzes Tokopedia's TVC advertising campaign version of "Pete's Philosophy" from the perspective of Komunikasi Berasa's theory with six dimensions: sensorial meaningfulness, emotional, rational, relevant, beneficial, and social. This advertisement is significant because it represents human insights closely related to consumers' problems, instincts, and daily lives, so the messages conveyed are relevant and authentic. This study's results inspire brands to create meaningful campaign messages as an effective way to steal audiences' hearts.